Electronic and Optical Properties of Cl-doped CH3NH3SnI3 Perovskite: A DFT Study - Laassouli Abdelmounaim; Moulaoui Lhouceine; Najim Abdelhafid; Archi Marouane; Karouchi Mohamed; Rahmani Khalid; Lachtioui Youssef; Bajjou Omar (E3S Web of Conferences)
Organic-inorganic hybrid perovskites have emerged as promising materials for photovoltaic applications. This study investigates the impact of chlorine (Cl) doping on the electronic and optical properties of the perovskite CH3NH3SnI3 (MA-SnI3) using density functional theory (DFT) calculations. We explore Cl doping concentrations of 8.33%, 16.66%, and 25%, analyzing the resulting changes in bandgap, density of states, and absorption coefficient. DFT calculations reveal a significant reduction in the bandgap with increasing Cl concentration, shifting from 1.055 eV for the methylammonium tin iodide structure to 0.727 eV, 0.731 eV, and 0.792 eV for the doped structures, respectively. Analysis of the density of states highlights the influence of Cl on the electronic structure. Furthermore, the absorption coefficient increases within the visible range, suggesting enhanced light absorption capabilities. Our results are consistent with experimental observations, validating the accuracy of DFT as a tool for studying Cl-doped MA-SnI3 perovskites and providing insights into their potential for solar cell applications.